Agency costs and credit availability: An international study - Mejda Bahlous-Boldi (European Journal of Management and Business Economics (EJM&BE), 2022)
Purpose - This paper aims to investigate the link between agency costs mitigation via three levels of rights protection (minority rights protection, enforcing contracts, resolving insolvency issues) provides the propitious climate for financing investment opportunities around the world. Design/methodology/approach - We use Bartlett's three-group method to stratify countries based on how well they protect investors as measured by the scores provided in the Doing Business dataset developed by the world bank for 189 countries. We then test a variety of independent hypotheses that the alleviation of agency costs via three levels of protection (minority investors' rights, contract enforcement, resolving insolvency issues) is associated with better access to credit via the banking system, better valuation of listed firms via the stock market and higher investment and growth. Findings - Our findings support Agency Theory which explains why the absence of legal protection of external investors leads to stock markets and financial institutions failing to fulfill their role of financing the economy. Practical implications - The policy implication from this study indicates that countries ought to (1) develop legislation that protects investors' rights, (2) improve the quality of their judicial system in terms of enforcing the legislation and (3) build the framework for resolving disputes during insolvency as these are important ingredients for a developed financial system. Originality/value - We use the World bank dataset and a new methodology to quantify the significance of the relationship between minority rights protection, ineffective enforcement, lack of bankruptcy laws and access to firm financing via the banking sector and the stock market. It provides new evidence that the quality of the judicial system in a country matter for firms' ability to raise financing and enhance value creation.
Keywords: 650; Agency Theory; Banking Sector development; Bankruptcy Law; Enforcing Contracts; Minority Investors; Shareholders' rights protection; Stock Market development